Assessing the results of general equilibrium studies of multilateral trade negotiations - Francois, Joseph (UN New YorkUS, 2000)
Looks at the Uruguay Round (UR) four years after implementation began, and how this compares to the calibration-based assessments that circulated at the end of the UR. Offers an overview of the CGE models employed or referenced by international organizations at the close of the UR. Presents a summary of the results of those models and a discussion of actual experience from UR implementation. Provides conclusions from this exercise and discusses recommendations for assessment of the next Round (or if not technically another 'round' of negotiations, then for the next sets of multilateral negotiations).